Circulating GLP-1 Levels in Patients with Pheochromocytoma/Paraganglioma - Chen, Nan; Chen, Yan; Lai, Fenghua; Chen, Li; Zeng, Rui; Pei, Ling; Wu, Liting; Wang, Chenxue; Li, Yanbing; Xiao, Haipeng; Cao, Xiaopei (International journal of endocrinology, 2022)
The sympathoadrenal system has been shown to stimulate the secretory activity of enteroendocrine cells, although the response is transient. Our aim was to investigate the effects of long-term catecholamine excess on circulating glucagon-likepeptide-1 (GLP-1) levels in patients with pheochromocytoma/paraganglioma (PPGL). Thirty patients diagnosed with PPGL were analyzed. A significant negative association was observed between fasting plasma GLP-1 levels and elevated plasma-free metanephrine (r=−0.407,p=0.026). After adjustment for age, sex, body mass index (BMI), serum creatinine, and the presence of hyperglycemia, the negative association between plasma GLP-1 and metanephrine persisted by multiple linear regression analysis (β=−0.493,p=0.013). Positive correlations between fasting glucose and plasma metanephrine (r=0.380,p=0.038) and normetanephrine levels (r=0.450,p=0.013) were also found. Mean fasting levels of total GLP-1 increased significantly from 25.81 to 39.01 pmol/L (p=0.017) after PPGL resection. In conclusion, long-term overproduction of catecholamines appears to induce suppression of GLP-1 production compared to an acute response to a stress stimulus. Further studies are required to elucidate the mechanism of GLP-1 secretion with chronic exposure to catecholamine.